Spatiotemporally anthropogenic PM2.5- and O3-related health economic losses via weather normalization technique and hierarchical policies in Chinese cities - Guo, Jinyuan; Wang, Teng; Li, Fei; Qu, Zhiguang; Yan, Jingjing; Kong, Shaojie (Frontiers in Ecology and Evolution, 2023)
With the promulgation of air pollution control policies, there are still many cities where the PM2.5 concentration exceeds 35 μg/m3, and O3 pollution is increasingly apparent. The spatio-temporal evolution and differentiation characteristics of PM2.5 and O3 pollution were explored, and then compound pollution hotspot urban agglomerations were screened out. A weather normalization technique was used to identify the driving amount, the influence of meteorological factors, and the anthropogenic emissions quantitatively, on pollution in hotspot urban agglomeration. Furthermore, the health and economic losses due to PM2.5 and O3 in hot cities in 2015–2020 were quantified. Finally, a natural break-point classification method was used to establish the health loss rating systems for PM2.5 and O3. The results showed the following: (1) From 2015 to 2020, 78%, 72%, 69%, 58%, 50%, and 41% of the annual mean PM2.5 concentration had exceeded 35 μg/m3, respectively, and 17%, 18%, 31%, 33%, 30%, and 17% of the annual mean O3 concentration exceeded 160 μg/m3, respectively, in 337 cities in China. (2) From 2015 to 2020, the health losses caused by PM2.5 and O3 were ranked as follows: Beijing–Tianjin–Hebei (BTH) (1968, 482 people) > Shandong Peninsula (SDP) (1396, 480 people) > Central Plains (CP) (1302, 314 people) > Yangtze River Delta (YRD) (987, 306 people) > Triangle of Central China (TC) (932, 275 people) > Guanzhong Plain (GZP) (869, 189 people). (3) The average economic losses associated with public health of the PM2.5 and O3 were ranked as follows: BTH (2.321 billion, 3.218 billion RMB, 1 RMB=0.0.1474 USD on 20 January 2023) > SDP (1.607, 2.962 billion RMB) > YRD (1.075, 1.902 billion RMB) > TC (1.016 billion, 1.495 billion RMB) > CP (1.095, 1.453 billion RMB) > GZP (0.69, 0.828 billion RMB). Therefore, combining hot pollution factors, the regional characteristics of the priority control areas, and the national 14th 5-Year Plan, targeted control countermeasures were proposed.